On behalf of tradition: An analysis of medical student and physician beliefs on how anatomy should be taught. Issue 8 (18th September 2015) - Marom, Assaf; Tarrasch, Ricardo
<x xml:space="preserve">Abstract</x> Human anatomy, one of the basic medical sciences, is a time‐honored discipline. As such, it is taught using traditional methods, cadaveric dissection chief among them. Medical imaging has recently gained popularity as a teaching method in anatomy courses. In light of a general tendency to reduce course hours, this has resulted in a decrease of dissection time and intense debates between traditional and modern approaches to anatomy teaching. In an attempt to explore trends in the attitudes of medical professionals toward the various methods of anatomy teaching, medical imaging in particular, the authors constructed a questionnaire and conducted a nationwide survey among medical students (in all stages at medical school), residents, and specialists in all fields of medicine. The survey results demonstrated indisputable appreciation of traditional methods of anatomy teaching, particularly cadaveric dissection, and showed that specialists believe significantly more strongly than clinical or preclinical students that anatomy and medical imaging should be taught separately. Strong correlations among the components of the traditional approach to anatomy instruction were also found. In light of the results, it was recommended that imaging should be incorporated into anatomy courses with caution, and, as far as possible, not at the expense of dissection time. It was advised that medical imaging has to be taught as a separate course, parallel to a traditional anatomy course. This will allow anatomical principles to be appreciated, which in turn will serve the students when they study radiology. "And we proceed in the following order: in front walks Nikolai with the slides or atlases, I come after him, and after me, his head humbly lowered, strides the cart horse; or else, if necessary, a cadaver is carried in first, after the cadaver walks Nikolai, and so on. At my appearance, the students rise, then sit down, and the murmur of the sea suddenly grows still. Calm ensues." —From "A Boring Story: From the Notebook of an Old Man" by Anton Chekhov. Clin. Anat. 28:980–984, 2015. © 2015 Wiley Periodicals, Inc.